Is there a minimum requirement for fat intake in athletic nutrition? - Tomten, S. E.; Høstmark, A. T. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
In contrast to extensive research on the significance of dietary carbohydrates and proteins for performance and health, the possible existence of a minimum requirement of fat in athletic nutrition has received little attention. The intake of important fat soluble vitamins may be limited when the nutritional content of fat is reduced, and increasing evidence of low dietary intake of vitamin E in modern Western societies has been presented within the general population. population (Maras et al., 2004). Additionally, a low fat diet is suspected to reduce the absorption and bioavailability of vitamin E ( Wolf, 2007), making dietary estimates an uncertain predictor for vitamin E status. Among the components of vitamin E in blood, alpha-tocopherol is the most potent antioxidant, protecting cell membranes from oxidative damage, and as athletic anemia has been frequently discussed, it was of interest to investigate if a low vitamin E bioavailability in athletes on a low fat diet could possibly cause damage to red blood cells. Subjects and Methods To investigate this aspect two groups of sub-elite athletes participated. One group had regular menstrual function R and the other was irregular (IR). The two groups had similar height, weight and athletic success. While intakes of protein and carbohydrates were similar and within normal range in the two groups, the daily intake of fat was significantly lower in the IR group (61± 6g; 1.1±0.1g/kg), than in the R group(98±12g; 1.7±0.2 g/kg). In order to determine the resistance of red blood cells to haemolysis, 13 participants, exercised for 20 min at the anaerobic threshold (HF =171±2 in R and HF = 172±3 in IR). Results Normal serum levels of alpha-tocopherol was found in the R group (27.3±3.6 micromol/L), while the IR group had a very low content (15.7 ± 0.8 micromol/L). In blood sampled after the exercise, osmotic fragility of red blood cells (%hemolysis) was found to be significantly negatively related to serum levels of alpha-tocopherol. Conclusion A low fat content in the food may indicate a reduced alpha-tocopherol levels in blood which seems to render the red blood cells more susceptible to haemolysis in connection with physical activity. This should be taken into account when nutritional guidelines are given. References Maras, J. E., Bermudez, O. I., Qiao, N., Bakun, P. J., Boody-Alter, E. L., & Tucker, K. L. (2004). Intake of alpha-tocopherol is limited among US adults. Journal of the American Dietetic Association, 104, 567-575. Wolf, G. (2007). Estimation of the human daily requirement of vitamin E by turnover kinetics of labeled RRR-alpha-tocopherol. Nutrition Reviews, 65, 46-48.